SELL WITHOUT LYING: THE ROLE OF AUTHENTIC MARKETING AND STORYTELLING IN PENTINGSARI TOURISM VILLAGE - Daniel Hermawan (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. Pentingsari Tourism Village is a tourist village located in Umbulharjo Village, Cangkringan District, Sleman Regency, Special Region of Yogyakarta. As Indonesia's flagship village that has won various awards, both nationally and internationally, Pentingsari Tourism Village has had its ups and downs when opening up to tourists. Carrying the live-in concept, Pentingsari Tourism Village tries to offer the experience of living with the local community with local activities that can be followed, starting from exploring the village nature, cultural arts, and village economy. Through an exploratory study conducted, researchers found the role of authentic marketing and storytelling as local advantages that were developed by the Pentingsari Tourism Village to attract tourists. Authenticity, honesty, and carrying a narrative story in telling the background of the activities and activities carried out in the Pentingsari Tourism Village provide a special experience for visitors who come. This research is expected to provide inspiration for tourist villages with similar conditions to develop authentic marketing and storytelling according to the situation and conditions of their respective geographical areas based on local capabilities. Abstrak. Desa Wisata Pentingsari merupakan desa wisata yang terletak di Kelurahan Umbulharjo, Kecamatan Cangkringan, Kabupaten Sleman, Daerah Istimewa Yogyakarta. Sebagai desa unggulan Indonesia yang telah meraih ragam penghargaan, baik secara nasional maupun internasional, Desa Wisata Pentingsari mengalami pasang surut ketika membuka diri untuk wisatawan. Mengusung konsep live in, Desa Wisata Pentingsari mencoba menawarkan pengalaman hidup bersama masyarakat lokal dengan aktivitas lokal yang dapat diikuti, mulai dari eksplorasi alam desa, seni budaya, dan ekonomi desa. Melalui studi eksploratif yang dilakukan, peneliti menemukan peran authentic marketing dan storytelling sebagai keunggulan lokal yang dikembangkan Desa Wisata Pentingsari untuk menarik minat wisatawan. Keaslian, kejujuran, dan pembawaan kisah yang naratif dalam menceritakan latar belakang aktivitas dan kegiatan yang dilakukan di Desa Wisata Pentingsari memberi pengalaman tersendiri bagi pengunjung yang datang. Penelitian ini diharapkan dapat memberikan inspirasi bagi desa wisata dengan kondisi serupa untuk mengembangkan authentic marketing dan storytelling sesuai situasi dan kondisi dari wilayah geografis masing-masing dengan berbasis kapabilitas lokal.